Prognostic Value of Pentraxin-3 Level in Patients with STEMI and Its Relationship with Heart Failure and Markers of Oxidative Stress. (1st April 2015) - Tomandlova, Marie; Jarkovsky, Jiri; Tomandl, Josef; Kubkova, Lenka; Kala, Petr; Littnerova, Simona; Gottwaldova, Jana; Kubena, Petr; Ganovska, Eva; Poloczek, Martin; Spinar, Jindrich; Mueller, Christian; et al.
Abstract : Objective . Pentraxin-3 (PTX3) appears to have a cardioprotective effect through a positive influence against postreperfusion damage. This study assesses the prognostic value of PTX3 level and its relationship with clinical parameters and markers of oxidative stress and nitric oxide metabolism in patients with ST-elevation myocardial infarction (STEMI). Methods . Plasma/serum levels of several biomarkers of inflammation and oxidative stress and nitrite/nitrate were assessed upon admission and 24 h after STEMI onset in patients treated by primary percutaneous coronary intervention. Results . ROC analysis showed that plasma PTX3 at 24 h was a strong predictor of 30-day and 1-year mortality and independent predictor of combined end-point of left ventricle dysfunction or mortality in 1 year. The inflammatory response expressed by PTX3 had a significant relationship with age, heart failure, infarct size, impaired flow in the infarct-related artery, and renal function and positively correlated with neopterin, TNF- α, 8-hydroxy-2′-deoxyguanosine, and nitrite/nitrate. Conclusions . Plasma PTX3 at 24 h after STEMI onset is a strong predictor of 30-day and 1-year mortality. PTX3 as a single biomarker is comparable with currently used scoring systems (TIMI or GRACE) or B-type natriuretic peptide. PTX3 is also an independent predictor of combined end-point of left ventricle dysfunction or mortality in 1 year.